Organizations or Social Movements? Outline of a Critique of a Conceptual Distinction. The Case of Social Organizations in Mexico City - Guerra Blanco, Edgar (Universidad del Rosario, 2014)
Along with social movements, social organizations in Mexico City have been key actors in the direction and consolidation of the liberalization and democratization processes of the Mexican political system and its main political and social changes. Moreover, the complexity of Mexico City and the variety of problems in it is, perhaps, an indicator of how diverse it is presented to the observer the field of social organizations. However, this article is concerned in grassroots organizations (Castells, 1988) especially those engaged in the protest as a form of communication. The question to answer is whether these organizations should be studied as organizations or as social movements and, once the choice has been made, if this means deciding between social movement’s theories or sociology of organizations. This article proposes an analytical model that looks at the case as organizations in protest, on the basis of a theory of social systems.